109k views
4 votes
Let g(x)=9x−10 and evaluate g(x+h)−g(x)/h

User Azamat
by
4.6k points

1 Answer

4 votes

Answer:


(g(x+h)-g(x))/(h)=9

Explanation:

we have


g(x)=9x-10

To find out g(x+h) substitute the variable x by the variable (x+h) in the function g(x)

so


g(x+h)=9(x+h)-10


g(x+h)=9x+9h-10

Evaluate


(g(x+h)-g(x))/(h)

we have


g(x+h)=9x+9h-10


g(x)=9x-10

substitute in the expression


(9x+9h-10-(9x-10))/(h)


(9x+9h-10-9x+10))/(h)


(9h)/(h)


9

therefore


(g(x+h)-g(x))/(h)=9

User Jmacedo
by
5.3k points